Legal Position Of A Person Who Is Not Attended (Afwezigheid) According To The Kuhperdata (Case Study At The Career Of Health Of Medan) - Jessica Vania Theresa Samosir (Journal of Law Science, 2021)
The development of technology and information does not guarantee that someone's whereabouts are unknown to others. Over time, it turns out that there is still a state of absence (afwezigheid), where a person's whereabouts are not known. With the condition of a person's whereabouts is not known by the family or community where he has committed a legal act, a problem will arise regarding the legal status of the person, this will relate to the interests of other people, namely the family left behind and will also intersect with various legal aspects, including the person's inheritance. The legal status of the person declared in a state of absence (afwezigheid),Based on this background, the issues raised are how the procedures for implementing and managing assets from an absence state (afwezigheid) by the Medan Heritage Property Center are held, what is the responsibility of the Medan Heritage Property Office in managing absenteeism fees (afwezigheid) and what is the role of the Medan Heritage Property Center in implementing and management of inheritance based on Court Decision Number 123/Pdt.P/2005/PN.TTD. The research method used in this study is descriptive analytical research, because it aims to describe the real situation, then the data obtained are analyzed qualitatively. Data were obtained through library research, namely collecting theoretical materials from the literature such as primary legal materials, secondary legal materials, and tertiary legal materials. The process of managing the assets of people who are not present (afwezigheid) is carried out starting from the recording stage to the stage of managing boedel in an absent state (afwezigheid). The responsibility of the Medan Heritage Treasurer in managing boedel absences (afwezigheid) is carried out until a period of 30 years and then becomes the property of the State, the role of the Medan Heritage Treasures in managing boedel absences (afwezigheid) based on Court Decision Number 123/Pdt.P/2005 /PN.TTD has been in accordance with the duties and functions of the Heritage Office.